Exploring entrepreneurial sustainability in a tourism practice: A transformative action research approach - Sifolo, P. P. S. (South African Journal of Higher Education, 2024)
Higher Education Institutions (HEI) play a significant role to unite diverse stakeholders and carry out planned learning activities that can promote change on both a personal and social level. Transformational research is dependent on the presence of an engaging and valuable problem that participants can make significant contributions in a collaborative manner across disciplines. Transformative learning process facilitates the integration of knowledge across several perspectives. This article explores the dynamic intersection of entrepreneurship and sustainability through the lens of a transformative action research approach in one’s teaching practice. A qualitative action research approach is adopted. This research aims to enhance Sustainable Entrepreneurship (SE) as a facilitator at the University and also synthesize insights from lived experiences in Finland, Namibia, Kenya, and South Africa. This article advocates for a transformative paradigm shift, to drive meaningful impact, foster resilience, and catalyse positive change in the pursuit of navigating entrepreneurial sustainable business practices as a facilitator.